THE IMPACT OF FİNANCİAL DEVELOPMENT LEVEL ON ECONOMİC GROWTH: BRICS COUNTRİES AND TURKEY ANALYSİS (Third Sector Social Economic Review, 2022)
The purpose of this study is to determine the relationships between financial development level and economic growth using the annual data 1990-2019 belong to BRICS countries and Turkey. In the study, economic growth was represented by the real GDP rate, while the degree of financial development was measured by the financial development index (FD). in order to examine the impact financial development level on economic growth and where a cause-and- effect relationship exist or not, panel causality analysis used. Afterward, the stationary of panel data is tested with CADF test which was created from Pesaran (2007). The outcome of CADF test demonstrates that all the variables are stationary at level. According to the findings of panel causality analysis, that there is a causality relation from financial development level (FD) to economic growth. But there is no any causality relation from economic growth to financial development level. So that the direction of the causality relationship between economic growth and financial development level is one-dimensional. So, nowadays economic growth and financial developments are the most discussed economic and finance issues in the world. Due to increased globalization, economists' research on the relationship between financial development and economic growth is considered to be of the utmost importance. As a result, research in this area is growing, and academicians are mostly interested in figuring out how financial development and economic growth are related.
Keywords: Financial Development (FD); Economic Growth; BRICS; CADF And Panel Data Analyzes